Mitigating transverse mode instability in fiber laser oscillator by employing direct pump modulation - Chai, Junyu; Liu, Wenguang; Wang, Xiaolin; Zhou, Qiong; Zhang, Jiangbin; Liu, Pengfei; Zhang, Hanwei; Lu, Yao; Zhang, Dan; Jiang, Zongfu; Zhao, Guomin (Frontiers in Physics, 2023)
The transverse mode instability (TMI) is a thermal-optical effect, inducing a sudden deterioration of beam quality and average power. This non-linear effect will greatly limit the power scaling of fiber lasers. We demonstrate a direct pump modulation to mitigate TMI in a 30 μm-core-diameter all-fiber laser oscillator. It only relies on function generator and pump drivers without the need of feedback control units. The groups of pump LDs and pump drivers and the phase difference between the channels of function generator have a great impact on the beam stability. Compared with the TMI threshold 180 W in continuous wave (CW) mode, the maximum average output power of a stabilized beam is increased up to 310 W via a multi-parameter-based direct pump modulation.